BUILDING COMMUNISM AND POLICING DEVIANCE IN THE SOVIET UNION;RESIDENTIAL CHILDCARE, 1958-91 - GALLEY, MIRJAM. (ABINGDON)
1 online resource
Keywords: This book examines, through a detailed study of Soviet residential childcare homes and boarding schools, the much wider issues of Soviet policies towards deviance, social norms, repression, and social control. It reveals how through targeting children whose parents could not or did not take care of them, as well as children with disabilities, the system disproportionately involved children from socially marginal and poor families. It highlights how the system aimed to raise these children from the margins of society and transform them into healthy, happy, useful Soviet citizens, imbued with socialist values. The book also outlines how the system fitted in to Khrushchev's reforms and social order policies, where the emphasis was on monitoring and controlling society without the recourse to direct repression and terror, and how continuity with this period was maintained even as the rest of Soviet society changed significantly.